1981
DOI: 10.1093/ajcn/34.9.1861
|View full text |Cite
|
Sign up to set email alerts
|

Effects of osmolality of liquid nutrient diets on plasma equilibration of water and carbohydrate in Yucatan miniature swine

Abstract: Osmolality of a liquid diet was varied from 250 to 700 mOsm/kg by altering the amount of sucrose and corn syrup solids, while maintaining the same level of calories, protein, and electrolytes. The appearance of 3H and 14C in blood plasma were monitored during a 4-h period after pigs voluntarily consumed one of five diets labeled with 3H2O and U-14C-sucrose. Plasma osmolality and sodium and potassium concentrations in plasma did not differ among the diets. Postprandial plasma glucose concentration response to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The second proposed way to adjust to isotonicity is via the absorption of solutes (25). After ingestion of a labeled diet (H2 0 and U'4C sucrose), rates of tracer appearance in blood plasma suggested that both water and carbohydrate absorption were accelerated with increasing osmolality.…”
Section: Nutrient Absorptionmentioning
confidence: 99%
“…The second proposed way to adjust to isotonicity is via the absorption of solutes (25). After ingestion of a labeled diet (H2 0 and U'4C sucrose), rates of tracer appearance in blood plasma suggested that both water and carbohydrate absorption were accelerated with increasing osmolality.…”
Section: Nutrient Absorptionmentioning
confidence: 99%
“…Within the first 120 min following the PS meal, the appearance of hydrolysis products in the digestive contents was paralleled by an increase in osmolality; osmolality has been shown to decrease the rate of gastric emptying [23], and to increase the rate of glucose absorption [4]. In the present study, we tried to relate the observed changes in duodenal osmolality after the PS meal to amylase activity.…”
mentioning
confidence: 93%
“…). 4 [6,11,18]. Moreover, fat [6] and proteins [30] [7], mixing the ingredients of the meal with water resulted in the formation of a gel.…”
mentioning
confidence: 99%